ANALYSIS OF PERFORMANCE AND EMISSION CHARACTERISTICS OF A DIESEL ENGINE FUELLED WITH BIODIESEL (Journal of Mechanical Engineering, 2017)
The rapid depletion in world petroleum reserves and uncertainty in petroleum supply due to political and economical reasons along with the sharp escalation in the petroleum prices have simulated the search for alternatives to petroleum based fuels especially diesel and gasoline. Moreover, bulks of petroleum fuels are being consumed by agriculture and transport sector for which diesel engine happens to be the prime mover. Though there are wide varieties of alternative fuels available the research has not yet provided the right renewable fuel to replace diesel. Vegetable oil due to their properties being close to diesel fuel may be a promising alternative for diesel engines. Due to their high viscosity, they cannot be directly used in a diesel engine. Transesterification is one method by which viscosity could be drastically reduced and the fuel could be adopted for use in diesel engine. Present investigation focuses on use of Rice Bran Oil in Diesel engine. Performance and exhaust emission characteristics of the engine have been evaluated. Esterified Rice Bran Oil has exhibited performance very close to that of diesel fuel. In the present work it is observed that, the NOX and unburned hydrocarbon emission decreases and carbon monoxide, particulate emission and smoke intensity increases with the use of biodiesel in diesel engine. When compared to non-esterified Rice Bran Oil, esterified Rice Bran Oil emits less smoke and therefore be regarded as an environment friendly fuel.